Sistem Informasi Administrasi Pada Kelompok Wanita Tani Laksmi Dewi Desa Ulakan - Suardana, I Made Eka; Sugiartawan, Putu (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2020)
The Women Farmers Group (KWT) Laksmi Dewi in Ulakan Village, most of whom are housewives, where this group is engaged in agribusiness development that aims to improve village food security. The activities of this group include the use of vacant land used as planting land, training on the use of agricultural land, and utilization of village resources related to agribusiness. KWT activities are generally funded from the organization's treasury which is sourced from government grants from the village, district, and provincial governments, funds from donors, remaining business proceeds, and other assistance funds. The problem that occurs is from administrative management to support group management. From this, it is recommended that a website-based administrative information system be the solution. This system will be designed and built in such a way that it can handle system functionality in the form of managing KWT members, managing KWT activities, and managing KWT funds related to income and sources of funds, utilization of funds and results or income from each activity.